2014
DOI: 10.1051/0004-6361/201322459
|View full text |Cite
|
Sign up to set email alerts
|

Mining the gap: evolution of the magnitude gap in X-ray galaxy groups from the 3-square-degree XMM coverage of CFHTLS

Abstract: We present a catalog of 129 X-ray galaxy groups, covering a redshift range 0.04 < z < 1.23, selected in the ∼3 deg 2 part of the CFHTLS W1 field overlapping XMM observations performed under the XMM-LSS project. We carry out a statistical study of the redshift evolution out to redshift one of the magnitude gap between the first and the second brightest cluster galaxies of a well defined mass-selected group sample. We find that the slope of the relation between the fraction of groups and the magnitude gap steepe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
88
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(95 citation statements)
references
References 105 publications
(142 reference statements)
7
88
0
Order By: Relevance
“…In the following sections, we will compare our candidate cluster catalogue to previously published cluster catalogues on the Wide fields of CFHTLS. We will first make a comparison with other optically detected cluster candidate catalogues from Licitra et al (2016) and Ford et al (2015), and with Xray detected cluster catalogues from Gozaliasl et al (2014) and Mirkazemi et al (2015).…”
Section: Amascfi Applied To the Cfhtls T0007 Data Releasementioning
confidence: 99%
See 3 more Smart Citations
“…In the following sections, we will compare our candidate cluster catalogue to previously published cluster catalogues on the Wide fields of CFHTLS. We will first make a comparison with other optically detected cluster candidate catalogues from Licitra et al (2016) and Ford et al (2015), and with Xray detected cluster catalogues from Gozaliasl et al (2014) and Mirkazemi et al (2015).…”
Section: Amascfi Applied To the Cfhtls T0007 Data Releasementioning
confidence: 99%
“…The Gozaliasl et al (2014) catalogue covers an area of 3 deg 2 inside the CFHTLS W1 field and includes 135 X-ray detected groups and clusters up to z = 1.1, while the Mirkazemi et al (2015) catalogue was built by pointing at given optically selected cluster candidates; it includes 196 X-ray detected groups and clusters up to z = 1.1 in the CFHTLS W1, W2, and W4.…”
Section: Matching Amascfi Cluster Candidates With X-ray Detected Clusmentioning
confidence: 99%
See 2 more Smart Citations
“…Jones et al (2003) reported 8% to 20% of all galaxy groups have the same X-ray luminosity as fossil groups. The redshift evolution of the fossil fraction has been studied by Gozaliasl et al (2014), finding that fossil groups constitute 22 ± 6% and 13 ± 7% of massive galaxy groups (M 200 ∼ 10 13.5 M h −1 ) at z ≤ 0.6 and 0.6 < z < 1.2, respectively. In the semianalytic halo catalogue, based on the Millennium simulation, ∼7.2 ± 0.2 per cent of massive groups are fossils (Dariush et al 2007).…”
Section: Introductionmentioning
confidence: 99%